Impressoras 3D para confecção de próteses de mão - Ohara, Lucas Eduardo Calabuig Chapina [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The objective of this study was to develop a low cost hand prosthesis made in a 3D printer. Research efforts focused on the development of a new design for the Raptor Hand prosthesis, aimed at implementing a fingertip force sensor and transmitting the captured signal to a circuit where the signal would be interpreted and converted into vibrations in a buzzer to provide feedback to the user of the force intensity being applied to the sensor. For implantation of the sensor in the prosthesis without interference in the capture of the signal by the rigid wall of the finger, it was implemented a flexible finger tip where the force sensor resistive (FSR) was allocated. The flexible material allowed a good positioning of the sensor in the prosthesis, besides not interfering in the capture of the signals by the sensor. The modifications resulted in a more functional prosthesis, providing a better user experience, without compromising the final cost of the prosthesis

O presente trabalho teve por objetivo o desenvolvimento de uma prótese de mão de baixo custo feita em impressora 3D. Os esforços da pesquisa se concentraram no desenvolvimento de um novo design para a prótese Raptor Hand, visando a implementação de um sensor de força na ponta do dedo e a transmissão do sinal captado até um circuito onde esse sinal seria interpretado e convertido em vibrações em um buzzer para fornecer um feedback ao usuário da prótese da intensidade da força que estava sendo aplicada ao sensor. Para a implementação do sensor na prótese sem que houvesse a interferência da captação do sinal pela parede rígida do dedo foi implementado uma ponta de dedo flexível onde o sensor de força resistiva (FSR) era alocado. O material flexível permitiu um bom posicionamento do sensor na prótese, além de não interferir na captação dos sinais pelo sensor. As modificações resultaram em uma prótese mais funcional, proporcionando uma melhor experiência ao usuário, sem comprometer o custo final da prótese
3D printers for making hand prostheses
Keywords: Prótese; Imagem tridimensional; Detectores; Prosthesis